Swine Flu (Influenza A, H1N1pdm2009) Infection on an Elderly Patient with Chronic Obstructive Pulmonary Disease (COPD): A Case Report - Anak Agung Bagus Bramardipa; Anak Agung Gde Upeksha (Faculty of Medicine Universitas Airlangga, 2023)
Introduction: Influenza is one of the most common causes of respiratory illness in the world. In April 2009, a novel H1N1 virus of swine origin was spreading among individuals, and within days became a pandemic, called H1N1pdm2009. Years after the pandemic, H1N1pdm2009 is now a common seasonal flu that manifests as flu-like symptoms just like other influenza. Swine flu is a self-limiting disease that doesn't need necessary antiviral treatment unless it displays moderate presentation or in an individual with comorbidities. Case: A 71-year-old man came to the emergency room with a chief complaint of shortness of breath. Symptoms started with common flu one week before admission and worsened prior the admission date. In the emergency room, patient looked lethargic, tachypnea, and low saturation, his oxygen saturation was 88% on room air and 99% using a non-rebreathing mask of 8 liters per minute. Ronchi was heard on both sides of the lungs. He has regular visits for his chronic obstructive pulmonary disease (COPD). Multiple investigations were done including thorax imaging, complete blood count and naso-orofaring PCR. Swab results indicated an influenza-A H1N1pdm2009 infection with no COVID-19 co-infection. During hospitalization, patient received a 75 mg dose of oseltamivir twice a day and other supportive treatment. The patient was discharged after five days of oseltamivir therapy with an improvement in conditions. Conclusion: Swine flu manifestation is similar to another influenza; however, in patients with comorbidities this virus can show moderate or severe presentation. Oseltamivir administration was given for five days and helped to improve the patient's condition.